Mechanisms of Selective Antitumor Action of Cold Atmospheric Plasma‐Derived Reactive Oxygen and Nitrogen Species. Issue 12 (14th October 2016) - Bauer, Georg; Graves, David B.
Abstract : Transformed cells are subject to elimination through intercellular reactive oxygen/nitrogen species (RONS)‐dependent apoptosis‐inducing signaling. Tumor progression, therefore, requires expression of membrane‐bound catalase. Recent research demonstrates that 1 O2 can inactivate membrane‐bound catalase, thus, inducing the generation of tumor cell‐derived secondary 1 O2 and RONS‐dependent apoptosis selectively in tumor cells. Crucially, 1 O2 signaling can result in self‐perpetuating apoptotic signaling from cell‐to‐cell. It is known that CAP contains 1 O2 and that certain CAP constituents can generate 1 O2 in solution. The analysis of model experiments performed with defined RONS implies that CAP‐derived 1 O2 induces the mechanism through which CAP acts selectively against cancer cells in vitro and tumors in vivo. This hypothesis needs to be tested experimentally in order to establish its validity. Abstract : The analysis of the reaction potential of reactive oxygen/nitrogen species from cold atmospheric plasma allows to propose that the presence of singlet oxygen can explain selective apoptosis induction in tumor cells in vitro and in vivo by cold atmospheric plasma. Singlet oxygen seems to inactivate membrane‐bound catalase of tumor cells, thus allowing the generation of secondary singlet oxygen and reactivation of apoptotic signaling in a self‐perpetuating mode.